2017
DOI: 10.1186/s12883-017-0871-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of video game therapy on balance and attention in chronic ambulatory traumatic brain injury: an exploratory study

Abstract: BackgroundPatients with traumatic brain injury often have balance and attentive disorders. Video game therapy (VGT) has been proposed as a new intervention to improve mobility and attention through a reward-learning approach. In this pilot randomized, controlled trial, we tested the effects of VGT, compared with a balance platform therapy (BPT), on balance, mobility and selective attention in chronic traumatic brain injury patients.MethodsWe enrolled chronic traumatic brain injury patients (n = 21) that random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…Therefore, in addition to impaired sensory integration, an elevated PPT could also stem from the deficits in attention that occur in 39-62% of TBI survivors (Marsh et al, 2016). Selective attention is essential for dynamic aspects of activities of daily living (Straudi et al, 2017) and individuals with balance impairments due to deficits in their automatic postural responses (APRs) (Woollacott and Shumway-Cook, 2002) rely more heavily on attentional mechanisms during standing. Attentional deficits post TBI and potentially impaired APRs due to impaired sensory integration could interfere with a TBI survivor's ability to safely complete motor tasks (Ponsford and Kinsella, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in addition to impaired sensory integration, an elevated PPT could also stem from the deficits in attention that occur in 39-62% of TBI survivors (Marsh et al, 2016). Selective attention is essential for dynamic aspects of activities of daily living (Straudi et al, 2017) and individuals with balance impairments due to deficits in their automatic postural responses (APRs) (Woollacott and Shumway-Cook, 2002) rely more heavily on attentional mechanisms during standing. Attentional deficits post TBI and potentially impaired APRs due to impaired sensory integration could interfere with a TBI survivor's ability to safely complete motor tasks (Ponsford and Kinsella, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Although video games were originally designed for entertainment purposes, a variety of auditory and visual sensory feedback systems have been developed specifically for balance rehabilitation and training [ 14 , 15 ]. Several recent studies have revealed that interactive video game-based (IVGB) exercises can ameliorate static and dynamic balance control in multiple sclerosis patients [ 16 ]; promote the correct weight shifting in stroke patients [ 17 ]; improve balance and attention deficits in chronic traumatic brain injury patients [ 18 ]; enhance functional balance and mobility in teenagers with cerebral palsy [ 19 ]. Some studies also suggested that IVGB exercise improve balance control, as well as self-reported balance confidence and mental health in healthy older population [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PICOS approach (Patients, Intervention, Control, Outcomes, and Study design) was followed (Liberati et al, 2009). Eight studies met the inclusion criteria (Peters et al, 2014;Damiano et al, 2016;Kleffelgaard et al, 2018;Cuthbert et al, 2014;Straudi et al, 2017;Cuff et al, 2014;Sveistrup et al, 2003;Thornton et al, 2005). A total of 259 patients post-TBI were included in this review, 71 (27.41%) of which were females.…”
Section: Participantsmentioning
confidence: 99%